The Impact of Multinationals on Labour Relations in Developing Countries: A Literature Review - Hassan Elsan Mansaray (Budapest International Research and Critics University, 2022)
The study discusses the impact of multinationals on labour relations in developing countries with special reference to Malaysia and Nigeria. The study discovered that several studies have been done on MNCs operating in Malaysia and revealed that the Malaysian government had used oppressive methods and strategies to keep trade unions in Malaysia dormant, so as to meet the urges of MNCs operating within the country. Malaysia has a history of no proper organized labour in the MNCs’ industries, because the managements of those industries are anti-union. Moreover, they just wanted to operate without any union interference, so that they can appropriate workers labour and maximized profit. For the case of Nigeria, there is organized and recognized labour but; their effort to protect members are sometimes dashed away by corrupt institutions that are empowered to monitor and evaluate MNCs activities. Bribery by MNCs to officials of these institutions have weakened the labour unions to carry out their mandate effectively. Hence, MNCs use the opportunity to override some labour laws like salary discrimination between expatriates and locals and ineffective human resource development. They usually fix higher salaries for their expatriates and low salaries for the local workers without being checked by the Nigerian authorities.